Respostas
respondido por:
0
Resposta:
Explicação passo a passo:
resposta na imagem
Anexos:
![](https://pt-static.z-dn.net/files/dc4/32bc6e61353fc43ac45fee3885410b79.jpg)
respondido por:
0
Resposta:
(-3, 1).
Explicação passo a passo:
x - 2y = - 5 ⇒ x = - 5 + 2y
2x + 3y = - 3
Substituindo x:
2(- 5 + 2y) + 3y = - 3
- 10 + 4y + 3y = - 3
4y + 3y = - 3 + 10
7y = 7
y = 7 : 7
y = 1.
x = - 5 + 2y
x = - 5 + 2 . 1
x = - 5 + 2
x = - 3.
Perguntas similares
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás